Mengapa Pecandu NAPZA Kambuh? Tinjauan Determinan Kekambuhan, Hambatan Akses, dan Peluang Farmakoterapi dalam Rehabilitasi di Indonesia - Sabrina Dwi Elvira; Gilbert Bastanta Sembiring; Alasen Sembiring Milala (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Substance use disorders (NAPZA) remain a major public health challenge in Indonesia, affecting an estimated 4.15 million people in 2025 and showing high rates of post-rehabilitation relapse. This review aimed to examine relapse determinants, barriers to rehabilitation access, and opportunities for pharmacotherapy in Indonesia. A narrative literature review was conducted using PubMed, Google Scholar, and Portal Garuda to identify studies published between 2015 and 2026. Nine studies met the inclusion criteria, comprising six cross-sectional, two case-control, and one qualitative study. The findings revealed significant systemic barriers, including limited rehabilitation capacity and inadequate cross-sectoral integration. Individual factors associated with relapse included low motivation, poor knowledge, hepatitis status, low self-efficacy, and high craving. Family-related factors, particularly inadequate emotional, social, and moral support, also significantly increased relapse risk. Environmental influences, such as peer pressure, easy drug availability, and direct drug exposure, further contributed to relapse. Pharmacotherapy options remain limited, with methadone maintenance therapy available on a restricted scale, while N-acetylcysteine and natural reward-based therapies have not been evaluated in Indonesia. Overall, relapse is driven by multidimensional factors, highlighting the need for integrated rehabilitation programmes combining pharmacological and psychosocial interventions to improve long-term recovery outcomes.